“Psychological Effect of Teaching English as A Second Language for Students with Disabilities” - Mamadiyeva Farangiz Baxtiyor qizi (Peerian Journals Publishing, 2022)
The article state information about psychological effect of teaching English for students with disabilities. It provides useful techniques and games that can be applied during teaching English
Keywords: pedagogical assistance; interaction strategy; inclusive education; communication